Improvement of Delivery Time at Y Group - Rachmanda, Reza; Hasan Basri, Mursyid (The Indonesian Journal of Business Administration, 2016)
Abstract. Y Group is a modern retail company in Bandung. They deliver products to their branch in West Java, Jakarta and middle Java. They have 35 branch throughout Bandung. To become the best retail, they always evaluate their performance each month. But in recent months Y Group distribution always late and resulted in unnecessary expenses. The most unnecessary expenses are in driverâ€™s overtime. It cost the company almost 20% to 30% of total expenses each month. Y Group already tracked and recorded the distribution process in the system so they know which part of the process that caused late delivery. Because of the business issue first identified from the late delivery, a conceptual framework is developed based on the factors that influencing late delivery. The factors are, distribution network, storage facility, inventory management, information and transportation. After the business analysis and ended with finding the root cause of the problem using current reality tree (CRT), there are six root cause that causing late in delivery. The cause are, flawed loading process, limited manpower at branch, flawed loading process, worker carelessness, unskilled worker and accident. There are internal root cause that will solve by Y Group distribution center and some external root cause that cannot be solve by Y Group because it is outside their control. The root cause that will not be discussed are limited manpower at branch and accident. After considering several alternatives for each root cause, there are three solutions that were chosen to solve the late delivery in Y Group. The solution for flawed loading process is to use a belt conveyor to help accelerate the loading process after consideration of cost, time and feasibility of the alternatives. The solution for flawed unloading process is to add more worker from the distribution center to the branch to help the unloading process. This alternative will accelerate the unloading process beside other alternatives after consideration of cost, time and feasibility. The last solution is to solve both the unskilled worker and worker carelessness because after the consideration of the alternatives the chosen alternative for both root cause is to conduct a training program.Â Keywords: modern retail, distribution, late delivery, distribution process